FIRST EXPERIENCES WITH OBJECT LESSONS IN NINETEENTH-CENTURY BRAZIL: ORIGINS OF A PROGRESSIVE PEDAGOGY FOR THE BRAZILIAN PRIMARY SCHOOL - M. Lorenz, Karl; Vechia, Aricle (Revista Diálogo Educacional, 2005)
One can identify two great movements during the nineteenth century in which educational theories and practices were transplanted from Europe and the United States to Brazil. The first addressed the secondary school curriculum, and began with the founding of the Imperial College Pedro II in Rio de Janeiro in 1838. The college was created by the Imperial Government to, in part, serve as a model for private and public secondary schools in the provinces. Throughout the 1800s, French curriculum theory shaped the debates about the purpose, organization and content taught in the College, and to a larger extent, about the nature of secondary education in general. The second transnational movement centered on the method of teaching in the primary school.